Combination of various grain sizes from nano to micron in polycrystalline holmium manganite (HoMnO3) as potential microwave absorbing application - M. M., Syazwan; A. N., Hapishah; I. R., Ibrahim; S. F., Nabilah (Springer Nature, 2019)
The combinations of various grain sizes from nano to micron in polycrystalline holmium manganite (HoMnO3) as potential microwave absorber were investigated. HoMnO3 was prepared via high energy ball milling pursued by sintering process. The phase analysis confirmed that the formation of hexagonal holmium manganite, HoMnO3 along with small amount of orthorhombic holmium dimanganese pentaoxide, HoMn2O5. SEM micrographs indicated larger grain size as the sintering temperature increased. Explicitly, HoMnO3 provides an electromagnetic (EM) wave absorption characteristics and it was found that HoMnO3 sample have a potential as an efficient microwave absorber which exhibited the maximum reflection loss value of—23.4 dB at 8.5 GHz. This study advocates that by combining different grain size (nano and micron size) would contributed an enhancement value of microwave absorption.